Illegal migration as a factor of security threat in Kosovo - Sylejmani, Rrahman; Maloku, Elda (Technium Social Sciences Journal, 2021)
In this paper it is analyzed the illegal migration which in the modern societies in recent decades is characterized with a great expansion, dynamic, organization and transnational connection. The research objects of this scientific paper are security challenges, risks and threats from illegal migration as well as the perception of the citizens of Pristina regarding the phenomenon and presence of illegal migration in Kosovo. In order to understand the opinion and perception of the citizens in the Republic of Kosovo regarding the presence of the illegal migration in Kosovo, a survey was conducted of 160 citizens of Pristina who answered 6 questions submitted through random method. Through this research it is intended to be understood first how much ordinary citizens have knowledge about the purpose of exploitation of victims by smugglers, what they may face during their journey, the factors that affect the occurrence of this phenomenon. Furthermore, raising the awareness of the citizens to cooperate with law enforcement agencies in cases of occurrence and investigation of migrants smuggling and also their awareness of the risk of possible terrorist attacks and the increasing crime rate that may carry the presence of these illegal migrants. The paper uses the survey method, the method of processing, analysis and interpretation of the obtained data as well as the comparative method.